Translation of Arabic Idioms into English: The Case of Amateur Subtitling - Yasser Muhammad Naguib Sabtan (Ijaz Arabi Journal of Arabic Learning, 2026)
Most studies on audiovisual translation focus on English-to-Arabic direction and little research has been conducted on the other Arabic-to-English direction. However, digital technology has increased the need for subtitling from Arabic into English as more and more Arabic-language movies and series are being subtitled and shown abroad. Amateur subtitling or fansubbing, which is a translation done by fans for other fans, has gained considerable attention recently. However, few studies have been conducted to investigate the amateur subtitling of Arabic movies and series into English. To address the paucity in this area of research, the present study is an attempt to explore the translation of Arabic idiomatic expressions, focusing on the strategies used by amateur subtitlers to render these expressions into English. Idioms are culture-specific expressions that are challenging for subtitlers. To achieve the study objective, three Egyptian movies translated by amateur subtitlers on YouTube were collected to examine the strategies used by fansubbers to translate Arabic idioms into English. The analysis of the examined data was conducted using Gottlieb’s model (1997) for the subtitling of idioms. The results of the study reveal that amateur subtitlers use a number of strategies to translate Arabic idioms into English. These are correspondence, paraphrase, congruence, omission, reduction and compensation. The analysis shows that the most frequently used strategies are correspondence (36.7%) and paraphrase (33.3%), which constitute 70% of the examples in the current study, while the least used are reduction and compensation, representing 3.3% for each of them. In addition, some of the analyzed subtitles are inappropriate translations of the Arabic idioms, as they are not communicatively translated into the target language.